Accessing hotel responsiveness towards guest's email query: cases in Malaysia - Anuar, Jazira; Jusoff, Kamaruzaman; Mahamed Ali, Faliza; Saien, Sairah; Md. Zaini, Zetty Madina; Khalid, Khazainah; Musa, Mushaireen (IDOSI Publications, 2011)
Information Technology (IT) has given tremendous positive effects in hospitality industry. It’s the most powerful weapon for hoteliers in order to stay competitive nowadays. One of the examples of technology that hit the hospitality world is e-mail. This study focused on three to five star hotels listed by the Ministry of Culture, Arts & Tourism of Malaysia that provide e-mail as a medium of communication and internet activity for its online patrons. Actual e-mail was sent to hotels asking for room availability, special room rate and facilities at the hotel. The implementation of technology in relation to customer service which is guest’s e-mail queries still remains unknown although technology initiation can be considered successful among hotels in Malaysia. As hoteliers, do they answer the guest’s e-mail queries promptly, politely and professionally?